THE ROLE OF SATISFACTION AND TRUST MEDIATE THE EFFECT OF SERVICE QUALITY ON CUSTOMER LOYALTY INDIHOME IN THE CITY OF DENPASAR - Ferdiansyah A.; Suprapti N.W.S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
Since the determination of Covid-19 as a pandemic by the World Health Organization (WHO), various public reactions have emerged. There are people who feel afraid, angry, panicked, confused, and sad about this pandemic. The government issued a number of policies, ranging from large-scale social restrictions called PSBB, to work from home, better known as WFH. Many customers have complained through Twitter social media because of dissatisfaction with the Indihome network, which had problems when carrying out work from home activities in the midst of the Covid-19 pandemic. The purpose of this study is to discuss the role of satisfaction and trust in mediating the effect of service quality on customer loyalty. The population in this study was Indihome customers in Denpasar City. The sample of this research are 160 respondents, the sampling method is non-probability in the form of purposive sampling. Testing the research hypotheses completed by using Structural Equation Modeling (SEM) analysis techniques based on Partial Least Square (PLS). The results showed that service quality had a positive and significant effect on customer satisfaction, trust and loyalty; and satisfaction and trust are able to mediate the effect of service quality on customer loyalty significantly. Satisfaction and trust in this study partially mediate. Theoretical implications can contribute to the existing literature, especially regarding service quality, satisfaction, trust and customer loyalty of Indihome. The practical implications of this research are expected to be able to contribute and understand the management of Indihome, especially in Denpasar City, regarding how satisfaction and trust mediate service quality on customer loyalty.